Restoring carbon accumulating processes in a degraded wet meadow - Baldwin, Lydia, author; Cooper, David, advisor; Steingraeber, David, committee member; von Fischer, Joseph, committee member (Colorado State University. Libraries, 2018)
Wet meadows throughout the Sierra Nevada range of western North America were historically disturbed and are thought to be losing soil water holding capacity and the ability to store carbon (C). I tested whether herbivore exclosures and the reestablishment of a sedge-dominated community at Tuolumne Meadows, a high elevation wet meadow in Yosemite National Park, can restore the C accumulating function of this ecosystem. In 2016, 20,000 Carex scopulorum (mountain sedge) were planted into the meadow. An empirical model of growing season carbon dynamics was created to determine if these treatments increase the meadow's C storage compared to controls. The second summer after planting, there was no difference in C storage capacity between treatment types and controls, and model estimates indicate that Tuolumne Meadows is a net source of carbon dioxide (CO2) to the atmosphere. Significant relationships between net ecosystem exchange (NEE) and percent vascular cover indicate that increasing vegetation cover could revert the ecosystem to carbon storing. However, future warmer, drier climatic conditions could maintain the system's current state as a C source.
Keywords: Sierra Nevada; wet meadow; carbon; Yosemite; wetland